Adherence and growth outcomes in children with growth disorders: results from the Easypod™ Connect Observational Study (ECOS) in Indonesia, Singapore, and Taiwan - Aman Bhakti Pulungan; Fabian Yap; Mei-Chyn Chao; Kah Yin Loke; Chen Yang; Tianrong Ma; Leroy Ovbude; Pen-Hua Su (Paediatrica Indonesiana, 2022)
Background Non-objective assessments indicate poor patient adherence to growth hormone (GH) prescribed for growth failure, with sub-optimal growth response. The easypod™ connect device for GH administration enables real-time, objective assessment of adherence. Objective To examine adherence with pediatric GH therapy in Asia-Pacific countries and relationship with growth outcomes. Methods Subjects were children in Indonesia, Singapore, Taiwan enrolled in the multi-national, open-label Easypod Connect Observational Study (ECOS). Adherence during follow-up was the primary endpoint and a relationship with 1-year growth outcomes was assessed by Spearman’s product-moment correlations. Results Over a 1-year time frame, median overall patient adherence was ?89%; rates were similar for children with GH deficiency (GHD; n=17) and those born small-for-gestational age (SGA; n=5), except that median adherence dropped between 9 months (94%) and 1 year (83%) for SGA subjects. Median initial GH dose was 42.3 ?g/kg/day for GHD subjects and 31.4 ?g/kg/day for SGA subjects. Median age (12 years) and bone age (13 years) indicated that most children had entered puberty at treatment onset. Clinically meaningful improvements in growth were observed at 1 year in the GHD group, but not the SGA group. Statistically significant correlations between adherence and height change (P=0.039) as well as height velocity (P=0.004) were observed. Conclusions Children in Asia-Pacific countries show high adherence over the first year of GH therapy with easypod. The easypod study also shows that adherence is correlated to good growth outcomes.